The influence of cash transfers on engagement in transactional sex and partner choice among adolescent girls and young women in Northwest Tanzania. Issue 1 (4th January 2022) - Gichane, Margaret W.; Wamoyi, Joyce; Atkins, Kaitlyn; Balvanz, Peter; Maman, Suzanne; Majani, Esther; Pettifor, Audrey
Abstract: Cash transfers are theorised to reduce adolescent girls and young women's economic vulnerability and engagement in transactional sex; however, the processes involved remain unclear. We conducted longitudinal cross-sectional, and narrative timeline in-depth interviews with young women aged 15–23 years in northern Tanzania enrolled in a cash transfer intervention. We analysed data using a thematic approach guided by the transactional sex framework. We summarised data and compared findings to the domains of the framework. Participants reported relationships in the 'sex and material expression of love' domain characterised by emotional intimacy and loose ties between material support and sex, and the 'sex for basic needs' domain characterised by limited emotional intimacy, economic vulnerability, and a clear exchange between material support and sex. Some participants expressed that cash transfers provided business capital and savings which enabled them to decrease 'sex for basic needs'. Cash transfers influenced transactional sex engagement by altering partner selection criteria such as from an emphasis on what men could provide to a focus on relationship stability. Findings suggest that cash transfers have the potential to reduce young women's transactional relationships motivated by economic vulnerability.